1999
DOI: 10.1051/analusis:1999270578
|View full text |Cite
|
Sign up to set email alerts
|

Development of new polymeric membranes for ENFETs for biomedical and environmental applications

Abstract: Two ways have been investigated for the preparation of urea ENFETs : covalent bonding of urease directly on the surface of an ammonium sensitive FET and control of the diffusion of charged species into the enzymatic layer on pH-ISFET using additional charged polymeric membranes. Trichlorfon as a representative pesticide is detected using a BuChE-FET sensor which is prepared either with cross-linked BSA-glutaraldehyde membrane or photocross-linkable PVA/SbQ (poly(vinyl alcohol) containing styrylpyridinium) memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In particular, the feasibility of miniaturization enables advanced applications, such as the surgical operations [ 1 ]. Enzyme field-effect transistors (EnFETs) are miniaturized biosensors which are typical ion-sensitive FET (ISFET) based biosensors, with an additional immobilized enzyme layer coating on the surface of gate dielectrics of a FET [ 2 6 ]. Those additional layers were fabricated on the supporting materials with entrapped enzyme coatings.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the feasibility of miniaturization enables advanced applications, such as the surgical operations [ 1 ]. Enzyme field-effect transistors (EnFETs) are miniaturized biosensors which are typical ion-sensitive FET (ISFET) based biosensors, with an additional immobilized enzyme layer coating on the surface of gate dielectrics of a FET [ 2 6 ]. Those additional layers were fabricated on the supporting materials with entrapped enzyme coatings.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that the current response increased linearly with glucose concentration at low concentrations, followed by a slower, non‐linear increase. Such results show a Michaelis–Menten dynamic characteristic 29…”
Section: Resultsmentioning
confidence: 74%
“…Such poor apparent enzyme activity agrees with the results obtained by Lillis et al 18, who compared BSA‐GA membranes with sol–gel membranes in a lactate oxidase immobilization network. Jaffrezic‐Renault et al 29 also reported lower sensitivity of a urea sensor when urease was immobilized in a BSA‐GA matrix compared to a nafion and photocross‐linked PVA/SbQ membrane. Even though GA cross‐linked PVA‐GOD membranes suppressed enzyme leakage earlier than the other methods, which suggested better enzyme retention and very high cross‐link densities, the tight network might have adverse effects on membrane permeability and the conformational configuration of the immobilized enzymes.…”
Section: Resultsmentioning
confidence: 98%
“…The application of ISFETs as ENFET biosensors is realized when pH changes near the gate are mediated by specific enzymes, in the presence of their substance in a dose-dependent manner [104]. Small molecules including glucose [105], urea [106][107][108], acetylcholine [109], creatinine [107] and cholesterol [110] have been widely investigated using ENFETs. Most recent research has focused on silicon nanomaterials [111][112][113], Au nanowires [114] and CNTs [115][116][117], and a few studies have investigated metal oxide semiconductors.…”
Section: Biosensors Based On Field Effect Transduction Field Effect Tmentioning
confidence: 99%